Moving towards homesourcing : an exploratory study on Singapore. - Lee, Wei Loong. (2009)
This report aims to study the amenability of homesourcing in Singapore and the possible implications for the various stakeholders, namely the government, organizations in Singapore and the people who work in Singapore. The project explores the future of homesourcing in Singapore through exploratory research. Through our research, we find that work practices in Singapore are indeed gradually shifting towards home-based work. The external employment environment (Political, Economic, Social, Technological, Legal and Environmental) suggest that employment practices are shifting towards flexible work while the internal environment (Organizational, Person and Task) suggest that work practices are shifting from office-based work towards home-based work. And through these findings, we proceeded to discuss the possible implications of growing home-based work to the Singaporean Government, the Singapore Organizations and the Singaporean People. In light of the lack of literature on this topic, our report serves to be an initial source of information for academics and practitioners alike. Also, in detecting these changes, we have also realized varying suitability towards homesourcing among industries and jobs and have thus drawn a list of industries and jobs most likely to be propensive towards homesourcing. Therefore, the report ends with a discussion on the possible preparatory measures that these industries and jobs and also the implicated governmental departments could take to suitably adjust to the growth of home-based work. Through our analyses, discussions and findings, we finally conclude that homesourcing is indeed amenable in Singapore and at the same time acknowledge that while the movement towards homesourcing is very likely, it will be a while before Singapore can truly embrace homesourcing.